If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -4 = 12x + 1 Reorder the terms: -4 + 11x = 12x + 1 Reorder the terms: -4 + 11x = 1 + 12x Solving -4 + 11x = 1 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -4 + 11x + -12x = 1 + 12x + -12x Combine like terms: 11x + -12x = -1x -4 + -1x = 1 + 12x + -12x Combine like terms: 12x + -12x = 0 -4 + -1x = 1 + 0 -4 + -1x = 1 Add '4' to each side of the equation. -4 + 4 + -1x = 1 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 1 + 4 -1x = 1 + 4 Combine like terms: 1 + 4 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| -4h+6k-2=5 | | -5y+7=-33 | | 8x=15x+22 | | 4ab-2bx=bx-ax+ax-bx | | 12x+1=11x-4 | | 0=3x-4-2y | | 4.6x=273 | | .04(y-2)+.18y=.08y-.01(50) | | 58=x-39 | | 34-2r=-4(4+3r) | | (w-0.44)(-0.67)=-0.8 | | -52-12= | | b+1=-14-4b | | 29+c=72 | | n-20=-2 | | 8x=4x+100000 | | 8-3*3+2= | | 60-x=251 | | g-e=r | | Q^2+4q-32=0 | | 30a^2+38a-20= | | (2x^2+3y)dx-(3x+4y^4)dy=0 | | 3m^3-9m^2+48m=0 | | (-6)2-(-4)+8= | | -12v+5=-19 | | -.5y+1=5.8-2y | | 0.35n=5.6 | | 2(4-y)=8-2y | | 78=66(-6a-5) | | 2(-1-4n)=28-2n | | 5m=4.5 | | 4x+1.50=21.50 |